The urban family, community and association a three-level communication analysis of family condominium interaction - Dela Cruz, Juan Miguel Calimon (2014)
"This thesis examines the communicative behavior of urban Filipino families living in condominiums. Urbanization has redefined the way families perceived housing with the construction of high rise condominiums; consequently, the interaction of families living in condominiums adapted to the condominium setup and developed new behaviors and perceptions with regard to interpersonal communication, sense of community and risk perception, as well as the message transmission within the association and maintenance of the community over time. To understand, at different levels, the communicative behavior of those living in condominiums, this thesis interprets insights, data trends, and document analysis. Urban Filipino families living in Greenhills Garden Square exhibited instrumental communication but was weak in exhibiting affective communication across all activities done by the respondents. Residents were indifferent with their neighbors, and was measured to have a low sense of community. The association, governed by the board of directors through the help of the administration, enforces rules and restrictions which ultimately directs how the community is maintained and managed. More importantly, this thesis raises the implications of condominium living on family communication, financial matters and issues on children and parenting among others."